VALIDITY THE ACID-BASE AND NEUTRAL PRACTICAL WORKSHEETS FOR STUDENTS IN GRADE VII SMP / MTS (Program Studi Pendidikan IPA FIP Universitas Hasyim Asy'ari, 2023)
Natural science is a discipline that requires practicum activities in its learning activities. Based on observations that practicum worksheets have never been developed by educators. This causes practicum activities in the school to be carried out according to the tools and materials available at school. Whereas in science learning, practicum activities are needed so that students better understand the science concepts studied. The purpose of this study was to describe the validity of acid-base and neutral practicum worksheets for grade VII SMP / MTs. This research is included in product development research using the ADDIE model. The research data was obtained through data collection using a questionnaire method addressed to respondents. This research instrument is a validation sheet that contains didactic, construction, language, content, and technical aspects. The results showed that the acid-base and neutral practical worksheets for students in grade VII SMP / MTs have met the validity and can be used in learning.